2015
DOI: 10.3389/fimmu.2015.00508
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Control of Mycobacterium tuberculosis by NK Cells: Role of Glutathione

Abstract: Tuberculosis (TB), caused by Mycobacterium tuberculosis (M. tb), continues to be one of the most prevalent infectious diseases in the world. There is an upward trend in occurrence due to emerging multidrug resistant strains and an increasingly larger proportion of immunocompromised patient populations as a result of the acquired immunodeficiency syndrome pandemic. The complex and often deadly combination of multidrug resistant M. tb (MDR-M. tb) along with human immunodeficiency virus (HIV) puts a significant n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 75 publications
1
92
0
3
Order By: Relevance
“…Consequently, it was postulated that GSH deficiency could lead to the progression of immune dysfunction, a hallmark of TB. 16,17 In the present study levels of GSH were found to be significant decreased in serum of TB infected individuals compared to healthy controls. Various studies showed that GSH play important role in TB.…”
Section: Discussionsupporting
confidence: 51%
“…Consequently, it was postulated that GSH deficiency could lead to the progression of immune dysfunction, a hallmark of TB. 16,17 In the present study levels of GSH were found to be significant decreased in serum of TB infected individuals compared to healthy controls. Various studies showed that GSH play important role in TB.…”
Section: Discussionsupporting
confidence: 51%
“…The ability to shift the redox homeostasis of the host is shared by many other viruses, bacteria and protozoa. As shown in Table 1, many infections caused by intracellular pathogens result in a 2-4-fold decrease in the GSH: GSSG ratio of the host cell221222324252627282930313233. Importantly, this altered redox state is often utilized by the pathogen to facilitate its pathogenesis and/or transmission.…”
Section: Resultsmentioning
confidence: 99%
“…NAC therapy can increase intracellular levels of GSH. 23,24 Devin Morris, et al mentioned in their research that NAC therapy can increase GSH levels and reduce intracellular MTB growth by increasing the function of the natural immune system by increasing macrophage activity. GSH can also control MTB by increasing the activity of T lymphocytes and NK cells.…”
Section: Nac In Tuberculosis a Nac As An Antioxidantmentioning
confidence: 99%
“…26 Figure 5. GSH increases NK cells cytolytic effectivity 23 Research by Vishwanath and colleagues suggests that NAC can control intracellular immunity more efficiently. NAC can also reduce the levels of proinflammatory cytokines, such as IL-6, TNFα, and IL-1 in TB patients.…”
Section: Nac In Tuberculosis a Nac As An Antioxidantmentioning
confidence: 99%